ANALYSIS OF THE CAUSES OF WAITING TIME FOR PATIENT TRANSFER IN THE EMERGENCY ROOM TO INPATIENT AND DISCHARGE HOSPITAL X MALANG CITY - Puspasari, Nuzulya; Ahsan; Khulud, Khoiron (Universitas Brawijaya, 2025)
Waiting time for patient services, especially in the Emergency Installation (IGD), which is the main entrance to the hospital, is one of the important aspects that affect the quality of service. The existence of patient complaints or dissatisfaction and the decline in quality and patient safety is one of the reasons for the long waiting time for patients in the emergency room. Based on the 2024 RS X quality indicator report, the waiting time for emergency room patients to be admitted to the hospital or go home ≤ 60 minutes is still 46.1% of the 100% target. The purpose of this study is to find out the cause of the long service process of emergency room patients being admitted to the hospital or going home. This research is qualitative research with a phenomenological approach. Data collection was carried out at Hospital X from September to October 2024 through in-depth interviews with informants and direct observation of the service process of emergency room patients before being admitted to the hospital or going home. The informants of this study are 6 management and staff of Hospital X related to the waiting time for emergency room patient services. The results of the research that were analyzed thematically revealed that there are 6 main root problems that cause the long waiting time for emergency room patients before being admitted to the emergency room or discharged, because there is no effective division of tasks and workflows in the emergency room, a lack of coordination between emergency room and inpatient officers, limited authority of assistant cashiers, an administrative flow of inpatient registration that is still inefficient, a lack of coordination between hospitals and insurance companies, and limited SIMRS features. The results of this study can be the basis for hospital management X in determining solutions to improve the achievement of waiting times for emergency room patients.